Implementasi Nilai-Nilai Karakter Religius melalui Kurikulum Sirah Nabawiyah di Pondok Pesantren Imam Bukhari, Karanganyar - Arsyad Shodiq; Joko Subando (Lembaga Yasin AlSys, 2026)
Although Sirah Nabawiyah has been widely studied as a medium for character education, research that specifically analyzes the implementation of its curriculum in the pesantren environment remains limited. This study aims to describe the concept and structure of the History of the Prophet (Sirah Nabawiyah) curriculum at Pondok Pesantren Imam Bukhari, Karanganyar, identify the religious character values contained in it, and analyze the implementation of these values in the learning process. This study used a descriptive qualitative approach with a case study design, involving ustaz/teachers and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation of the curriculum and reference books, and were then analyzed using the Miles and Huberman interactive model with source and technique triangulation to ensure data validity. The results showed that the Sirah Nabawiyah curriculum in the pesantren integrated five main religious character values, namely honesty (ṣidq), trustworthiness (amanah), patience, responsibility (mas’ūliyyah), and role modeling (uswah ḥasanah), through the delivery of material, habituation, and the role modeling of ustaz, supported by a religious pesantren environment. These findings contribute to the development of Islamic character education by combining Ibn Qayyim al-Jawziyyah’s concepts of habituation and role modeling with Thomas Lickona’s framework of moral knowing, moral feeling, and moral action. The conclusion of this study affirms that role modeling based on the Sirah Nabawiyah curriculum plays an important role in shaping students’ religious character. The implications of this study include theoretical contributions to the development of Islamic character education literature as well as practical implications for pesantren in designing Sirah Nabawiyah learning that is more varied, participatory, and oriented toward the internalization of religious values.